Urban expansion indicators of cities "Case study for Arab cities - Nabil T. Ismael (Journal of Techniques, 2020)
Urban population growth requires an appropriate and suitable place for future population to cope with the expected urban expansion of major cities in developing countries, and to identify an indicator urban expansion to guide planners, architects and decision makers, and help them reduce negative effects of city expansion with improvement in the ability to live in cities. The density (population and building), fragmentation (saturation and openness) and compactness (proximity and cohesion) are the most important indicators of urban expansion of cities, which gives a clear perception of how city expands and possibility of adopting the most suitable ones when updating or preparing master lans. Most cities, especially Arab ones, suffer from excessive urban expansion, resulting in various urban problems affecting quality of life, services and city performance, which is the problem of research. This research is aimed at identifying factors influencing urban expansion of cities in developing countries when preparing for their future expansion, by analyzing the indicators of urban expansion of a set of cities to reach appropriate indicators for urban expansion sustainable future of the city to ensure orderly development of cities and make them more productive, more comprehensive and sustainable in upcoming decades.